Adsorptive Removal of Methylene Blue and Crystal Violet onto Micro-Mesoporous Zr3O/Activated Carbon Composite: A Joint Experimental and Statistical Modeling Considerations - H. Ait Ahsaine; Z. Anfar; M. Zbair; M. Ezahri; N. El Alem (Journal of Chemistry)
Zirconium oxide/activated carbon (Zr3O/AC) composite was synthesized to remove methylene blue (MB) and crystal violet (CV) from the aqueous medium. The Zr3O/AC sample was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray analyses (EDS), Raman spectroscopy (RS), BET surface area, and Fourier transform infrared spectroscopy (FTIR). XRD profiles confirmed the successful synthesis of the zirconium oxide/activated carbon composite. SEM images showed multideveloped walls with irregular particle size with channel arrays. The nitrogen physisorption combines I and IV types with a calculated BET surface area of 1095 m2/g. Raman spectrum illustrated a disorder of both crystalline structure and the graphitic structure. The adsorption was better fitted to the pseudo-second-order (PSO) kinetic model. Langmuir model fitted better the experimental results of MB adsorption, whereas the CV was better consistent with the Freundlich model. The obtained results suggested that the MB and CV adsorption might be influenced by the mass transfer that involves multiple diffusion steps. The maximum adsorption capacities are 208.33 and 204.12 mg/g for MB and CV, respectively. The MB and CV removal mechanisms were proposed, and statistical optimization was performed using central composite design combined with the response surface methodology.